2022
DOI: 10.1016/j.mtbio.2021.100189
|View full text |Cite
|
Sign up to set email alerts
|

Cascade targeting codelivery of ingenol-3-angelate and doxorubicin for enhancing cancer chemoimmunotherapy through synergistic effects in prostate cancer

Abstract: Immunotherapy has led to an expansion of the treatment of malignancies, but its effect in prostate cancer (PCa) patients is modest. Chemoimmunotherapy is a promising approach that has attracted substantial attention. Although the widely used clinical chemotherapeutic drug doxorubicin (DOX) elicits immunogenic cell death (ICD), its weak ICD effect and the abnormal vasculature of tumors severely limit its efficacy in chemoimmunotherapy. Ingenol-3-angelate (I3A), an emerging antitumor drug with dual chemotherapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Through the analysis of drugs whose sensitivity may be related to SLC1A5 expression, we found that ingenol, prostratin, and parthenolide can be used as potential small molecule drugs for cancer treatment. A previous study showed that ingenol induces immunogenic cell death of prostate cancer cells by triggering mitophagy and apoptosis, promotes the normalization of tumor blood vessels, and allows immune cells to fully infiltrate the tumor, thereby exerting antitumor effects [ 58 ]. Therefore, it can be determined that ingenol, as an emerging antitumor drug, can affect the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Through the analysis of drugs whose sensitivity may be related to SLC1A5 expression, we found that ingenol, prostratin, and parthenolide can be used as potential small molecule drugs for cancer treatment. A previous study showed that ingenol induces immunogenic cell death of prostate cancer cells by triggering mitophagy and apoptosis, promotes the normalization of tumor blood vessels, and allows immune cells to fully infiltrate the tumor, thereby exerting antitumor effects [ 58 ]. Therefore, it can be determined that ingenol, as an emerging antitumor drug, can affect the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also detected the stability of the HT@PTX and HT@ER/PTX in different conditions in vitro according to the protocol described in Ref. [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The delivery of these nanomedicines resulted in a potent antitumor immune response as well as reduced tumor development. It demonstrated that I3A blocked VEGF expression in tumor cells to restore normal tumor vasculature and induced mitophagy and death in human and mouse prostate cancer cells [ 91 ].…”
Section: Prostate Cancer Treatment By Novel Drug Delivery Systemmentioning
confidence: 99%